The Influence of Social Media, Motivation, and Creativity on Entrepreneurial Ability of MSEs in Kembangan Village, Kebomas District, Gresik - Dinda Ayu Latifah; Rachmad Ilham; Umar Burhan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of social media, motivation, and creativity on entrepreneurial skills in Micro and Small Enterprises (MSEs) in Kembangan Village, Kebomas District, Gresik. MSEs play a crucial role in improving the community's economy, but still face various limitations in terms of both access to resources and entrepreneurial capacity development. Therefore, this study was conducted to determine the extent to which personal factors such as social media utilization, motivational drive, and creativity can contribute to the entrepreneurial skills of MSEs. This study used a quantitative approach, collecting data through a structured questionnaire from 100 registered MSEs in the study area. The data were analyzed using multiple linear regression with SPSS version 25 software. The results showed that social media, motivation, and creativity did not significantly influence entrepreneurial skills, either partially or simultaneously. The coefficient of determination (R²) was 0.073, or 7.3%, indicating that the model only explains a very small proportion of the variation in entrepreneurial skills. These findings suggest that factors beyond the research variables, such as market access, availability of business training, and financial support, likely exert a more dominant influence on the development of entrepreneurial skills among MSEs in rural and peri-urban areas. Therefore, efforts to increase entrepreneurial capacity cannot rely solely on individual factors but also require integrated structural interventions. Synergy between strengthening personal competencies, government policy support, providing funding facilities, and expanding market access is crucial for creating a sustainable entrepreneurial ecosystem. This research is expected to provide input for local governments, MSE support institutions, and academics in formulating more effective and targeted MSE development strategies.